2019
DOI: 10.1007/s00167-019-05617-w
|View full text |Cite
|
Sign up to set email alerts
|

More pain and slower functional recovery when a tourniquet is used during total knee arthroplasty

Abstract: Purpose Although a tourniquet can effectively control intraoperative blood loss and offer clear surgical field in total knee arthroplasty (TKA), its optimal usage has been controversial. The aim of this research was to perform a systematic review and meta‐analysis to compare and explore the best application of a tourniquet in TKA. Methods MEDLINE, PubMed, EMBASE, the Cochrane Library, Wanfang database, and Web of Science were searched for randomized controlled trials (RCTs) comparing the four different strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
(235 reference statements)
4
34
3
Order By: Relevance
“…Besides this, tourniquet use in TKA may be related to increased postoperative knee pain and swelling. A systematic review and meta-analysis of 46 RCTs demonstrated that tourniquet use in TKA caused more pain [29]. Moreover, two studies [30,31] reported that tourniquet application in TKA was associated with a higher opioid consumption, which equates to increased pain related to tourniquet use.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, tourniquet use in TKA may be related to increased postoperative knee pain and swelling. A systematic review and meta-analysis of 46 RCTs demonstrated that tourniquet use in TKA caused more pain [29]. Moreover, two studies [30,31] reported that tourniquet application in TKA was associated with a higher opioid consumption, which equates to increased pain related to tourniquet use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Zhang et al [3] in 2017 from eight studies comparing incision-to-suture versus a full-time tourniquet regime. Likewise, in 2019, Liu et al [84] analysed operating times across several tourniquet protocols, evidencing significantly longer surgeries in the absence group compared to the fulltime tourniquet group (P = 0.005). On the other hand, Wang et al [12] found no difference in surgical duration between shorter tourniquet use during cementation only and longer tourniquet use across 338 procedures; however, their findings were compromised by a high level of heterogeneity across the data.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that long-term use of tourniquet can reduce intraoperative and intraoperative total blood loss, while short-term use of tourniquet can reduce postoperative and postoperative hidden blood loss without increasing the rate of allogeneic blood transfusion [23]. Interestingly, some studies found that 48 h after total knee arthroplasty, the strength of knee extension was not superior in the group without tourniquet, but tourniquet caused lower limb pain [24,25]; others suggested that the use of tourniquet had no signi cant correlation with postoperative rehabilitation [26]. In summary, studies on tourniquet use or not have been reported, but there is little literature comparing postoperative rehabilitation with limited tourniquet use versus no tourniquet use.…”
Section: Discussionmentioning
confidence: 99%